The Group of 77 and global dialogue in the United Nations General Assembly - Max-Otto Baumann; Anna Novoselova; Javier Surasky; Philipp Schönrock (German Institute of Development and Sustainability (IDOS), 2024)
Relations between the global North and global South have grown more contentious in recent years. As frustration rises in tandem with global power shifts, the United Nations (UN) has become an arena for the negotiation of a new global governance. Within this framing, the Group of 77 (G77), comprising some 80% of the global population from 134 developing countries, plays an important role for UN multilateralism. The group has over time become more complex, diverse and assertive in promoting its interests and shaping UN processes and policy vis-à-vis its longstanding counterpart, the global North. Global North countries register confrontational diplomatic practices by the global South that challenge their predominant roles. Reaching consensus seems to have become more challenging, as suggested by observing processes such as the Summit of the Future, which have been marked by stalemate due to conflicting interests. Still, relatively little is known about the internal decision-making of the G77. It is against that backdrop that the discussion paper - a collaboration of IDOS and the Colombian think tank Cepei - examines the G77's internal structure, decision-making, and power distribution, and how these are factors for global dialogue in the UN.
Keywords: 320; Group of 77; Global South; United Nations; General Assembly; North-South-conflict